Political-administrative leadership for the 21st century - Abueva, Jose Veloso (Philippine Journal of Public Administration, 1997)
The only constant thing in life, politics and administration included, is change. So do the roles, standards and conditions of political-administrative leadership change. Also, the leaders of the next millennium must review and evaluate, and if necessary alter their current roles and qualification in order for them to face decisively the challenges of tomorrow.